2001
DOI: 10.21273/horttech.11.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial Substrate Depth on Freezing Injury of Six Herbaceous Perennials Grown in a Green Roof System

Abstract: A green roof system was installed on an existing 35-year-old building. The purpose of the study was to evaluate the effect of three substrate depths on low-temperature injury of six herbaceous perennials: bugleweed (Ajuga reptans), sandwort (Arenaria verna `Aurea'), sea pink (Armeria maritima), whitlow grass (Draba aizoides), creeping baby's breath (Gypsophila repens), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 4 publications
3
63
1
7
Order By: Relevance
“…Generally, green roofs are likely to have greater fluctuations of soil temperature and soil moisture than in a greenhouse, especially thin substrates (Boivin, Lamy, Gosselin, & Dansereau, 2001) because of more frequent irrigation, irregular rainfall, strong wind and high radiation on roofs. In the UK, for example, rainfall is frequent and this would be associated with a greater frequency of the drying and wetting cycle, and hence lush growth with high organic matter content could be a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, green roofs are likely to have greater fluctuations of soil temperature and soil moisture than in a greenhouse, especially thin substrates (Boivin, Lamy, Gosselin, & Dansereau, 2001) because of more frequent irrigation, irregular rainfall, strong wind and high radiation on roofs. In the UK, for example, rainfall is frequent and this would be associated with a greater frequency of the drying and wetting cycle, and hence lush growth with high organic matter content could be a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh mass (g) Dry mass ( fluctuations in temperature (Boivin et al, 2001). However, there are reports with contradictory results in Sedum acre and Arabidopsis thaliana, which showed similar or even bigger plant growth in shallower substrates Olly et al, 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…Deeper substrate also maintains more stable soil temperature and provides larger space for roots of green roof plant. Boivin et al (2001) found that shallower substrates in extensive green roof experience much more severe temperature fluctuations than deeper substrates. However, there are no published studies on the effects of substrate depth on root morphology and distribution and their relationships to plant drought tolerance in green roof.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all published studies which focus specifically on green roof plants are concerned with plant selection in terms of survival of the environmental stresses of the roof environment (e.g. Boivin et al 2001;Dunnett and Nolan 2004). An exception is the study of Monterusso et al (2004), which tested the influence of four different commercial green roof systems on the quantity of stormwater runoff from that system.…”
mentioning
confidence: 99%